Companionship of the French education model and the idea of national unity in modern Iranian education: From Constitutionalism to September 1941 - R. Mahoozi (Taḥqīqāt-i Farhangī-i Īrān, 2020)
The issue as why and how the modern educational system of Iran that simultaneously kicked off with the establishment of Dār-al-Funun (the Academy of Arts ) in 1941 could gradually come under the dominance of the French educational system but fell into the domain of nationalism in the late Qajar period and throughout the first Pahlavi era, and that, when and to what extent these two formal and content areas could involve the modern educational system of Iran is the subject the author intends to show their connection through historical sources as well as documents and analyses in this domain. To respond to the aforementioned questions, it is essential to know which of the characteristics of the French educational system was associated with patriotic tendencies of Iranians in the late 19th and early 20th centuries, which, too, were not unaffected by transformations in Europe and West Asia. This article will show Iran’s internal requirements, including domestic and border security, cultural and economic transformation as well as medical necessities, along with the historical context of Iranians' attention towards France and its well-known revolution, during Ahmad Shah Qajar, a period also known for the constitutional consolidation. To bring into account the political, cultural, and economic system led to the fact that the central government should realize the aspiration of constitutionalists by adopting cultural unification under the idea of ​​national unity and the plan of modernity, with the help of two tools i.e. modern education and bureaucracy.